2018
DOI: 10.1113/jp276694
|View full text |Cite
|
Sign up to set email alerts
|

Spinal plasticity with motor imagery practice

Abstract: Key points While a consensus has now been reached on the effect of motor imagery (MI) – the mental simulation of an action – on motor cortical areas, less is known about its impact on spinal structures. The current study, using H‐reflex conditioning paradigms, examined the effect of a 20 min MI practice on several spinal mechanisms of the plantar flexor muscles. We observed modulations of spinal presynaptic circuitry while imagining, which was even more pronounced following an acute session of MI practice. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 55 publications
3
51
0
Order By: Relevance
“…Our results showed, regardless of task dynamics, a high temporal correspondence between them. This isochronism extends previous findings that reported comparable durations of actual and mental movements (Gentili et al, 2004;Guillot and Collet, 2005;Papaxanthis et al, 2012) and reinforces the well-documented idea of a similar neurocognitive network between actual and mental states (Grosprêtre et al, 2019;Ruffino et al, 2017). Temporal similarities between actual and mental movements reinforce the idea that the brain preserves an accurate internal model of arm and environmental dynamics.…”
Section: Discussionsupporting
confidence: 90%
“…Our results showed, regardless of task dynamics, a high temporal correspondence between them. This isochronism extends previous findings that reported comparable durations of actual and mental movements (Gentili et al, 2004;Guillot and Collet, 2005;Papaxanthis et al, 2012) and reinforces the well-documented idea of a similar neurocognitive network between actual and mental states (Grosprêtre et al, 2019;Ruffino et al, 2017). Temporal similarities between actual and mental movements reinforce the idea that the brain preserves an accurate internal model of arm and environmental dynamics.…”
Section: Discussionsupporting
confidence: 90%
“… b ) with an interstimulus interval of 20 ms, reported as the most effective delay to ensure a large inhibitory effect on the conditioned H‐reflex (Grospretre et al . ). Ten conditioned H‐reflexes ( H D1 ) were recorded at 5–10 s intervals for PRE and POST measurements (Fig.…”
Section: Methodsmentioning
confidence: 97%
“…the lowest intensity that evoked at least three M-waves out of five stimulations (mean M-waves were 0.68 ± 0.36 mV and 0.59 ± 0.33 mV for S H depress and S H match sessions, respectively). Then the SOL H-reflex (using the stimulation intensity determined for H TEST ) was conditioned by a prior stimulation of the fibular nerve (Mizuno et al 1971;Hultborn et al 1987b) with an interstimulus interval of 20 ms, reported as the most effective delay to ensure a large inhibitory effect on the conditioned H-reflex (Grospretre et al 2018). Ten conditioned H-reflexes (H D1 ) were recorded at 5-10 s intervals for PRE and POST measurements ( Fig.…”
Section: Experimental Designmentioning
confidence: 99%
“…These regions include the supplementary motor area (SMA), premotor cortex (PMC), primary motor cortex (M1), posterior parietal regions (e.g., the inferior and superior parietal lobes), the basal ganglia (BG) and cerebellum (see Hardwick et al, 2018). Furthermore, evidence demonstrates that MIP not only activates motor cortical and subcortical regions but also induces plastic change in motor networks and modulates synaptic activity at the spinal level (e.g., Debarnot et al, 2014;Grosprêtre et al, 2019). Interestingly, the latter effect indicates that motor commands are issued during MI and while they remain subthreshold for physical movement, they have the capacity to influence spinal cord activity (Grosprêtre et al, 2018(Grosprêtre et al, , 2019.…”
Section: Explaining Mip Effects: Motor Simulation Theorymentioning
confidence: 99%